The Weight Efficiency of Steel Framed Buildings with Various Wind Bracing Systems - Abbassi, Sanaz Khoddam (Eastern Mediterranean University (EMU), 2009)
ABSTRACT: This research is about the efficiency of using different types of wind bracing and with different steel profiles for bracing members for multi-storey steel frames. ETABS software was used to obtain the design of frames and bracing systems with the least weight and apropriate steel section selection for beams, columns and bracing members from the standard set of steel sections. The design loads are specified in BS 5950 (2000). The serviceability limit state included in the design problem is achieved by limiting the overall and intermediate storey lateral displacement in the building to height/300 as specified by the code. Bracing members are considered to be made of Universal Angle section [Equal Angle (EA) and Unequal Angle (UA)], Rectangular Hollow section (RHHF), Circular Hollow section (CHHF) and I section [Universal Column (UC)]. This research presents the design of steel structure subjected to wind loading for buildings up to 5, 10, 15 and 20 stories with symmetrical plan and section, asymmetrical plan and section, symmetrical plan and asymmetrical section and asymmetrical plan and symmetrical section steel frame buildings with different bracing systems such as cross, zipper and knee bracing at the core and central bay of the structure. From this research it is concluded that Rectangular Hollow Section zipper bracing produces the lightest frame among the others. Keywords: Braced steel frames; Bracing systems; Wind loads; Weight of steel elements; Lateral displacement. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZET: Bu arastırma çok katlı çelik çerçevelerde hangi tip rüzgar bağ sisteminin daha etkili çalısabileceğini ve bu bağ sistemlerinde kullanılan çelik profilleri incelemek için yapılmıstır. Bu amaçla çelik çerçeve tasarımı için ETABS programı kullanılmıs ve tasarıma en uygun profiller programda yer alan standard tablolardan seçilmistir. Kiris kolon ve bağ sistem elemanları için seçilmistir. Tasarımda kullanılan yükler ingiliz çelik standardı BS5950 (2000)’den alınmıstır. Bu kodun önerdiği her kat için yatay öteleme limiti olan kat yüksekliği / 300 her bir katın ve tüm binanın yatay ötelemesini kısıtlamak için kullanılmıstır. Böylece yatay yönde gerekli sağlanmıstır. Bağ sistem elemanları için kösebend, dikdörtgen ve daire profil ve I-profil kolon kullanılmıstır. Bu arastırmada 5, 10, 15 ve 20 katlı simetrik plan ve kesiti, asimetrik plan ve kesiti simetrik plan ve asimetrik kesiti, asimetrik plan ve simetrik kesiti olan, çelik yapılar tasarlanmıstır. Göbeğinde ve orta açıklıklarında farklı bağ sistemleri kullanılmıs, örneğin çapraz, ters V ve dısmerkezli bağlanmıs çelik yapılar tasarlanmıstır. Elde edilen sonuçlar doğrultusunda dikdörtgen profil kullanılan ters V bağ sisteminin tüm sistemler arasında en hafif çerçeveyi verdiği görülmüstür. Anahtar kelimeler: bağlanmıs çelik çereçeve, bağ sistemleri, rüzgar yükleri, çelik elemanların ağırlıkları; yatay öteleme.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2009. Supervisor: Assist. Prof. Dr. Mürüde Çelikağ.
Keywords: Civil Engineering; Braced Steel Frames - Bracing Systems - Wind Loads - Weight of Steel Elements - Lateral Dispacement